The Row Material Policy In Poor And Small Countries - Lilia ŞARGU; Alexander GRIBINCEA; Vadim ALEXEENCO (Eastern European Journal of Regional Studies)
The major tasks concerning economic diversification and modernization mean the importance of priorities for foreign policy regarding economic diplomacy. Thinking about the governmental tasks for prioritizing directions of foreign trade activities, by attracting international investors, by upgrading technology, importing advanced foreign technologies, exporting development, and promoting national economic interests abroad. The Governmental structures and authorized institutions always relay on importance for external economic policy, focusing on achieving concrete economic results. In a globalized industrialization, tasks of economic modernization, development of the resource and infrastructure establishing for the Ministry of Foreign Affairs and European Integration, tasks that require intensification of economic cooperation in a widespread area. The particular importance in this research has the close relationship between cooperation within international organizations with universal or regional interests. Achieving the objectives of economic diplomacy will help improve the competitiveness of the economy ultimately, create new industries and jobs and economic growth of the country as a whole.